Academic celebrity - Walsh, P; Lehmann, D (Springer, 2019)
This article examines the institution of celebrity within academia. Academic celebrity has parallels with the celebrity seen in the wider world, though it is born of conditions unique to the fields of higher education and research and exhibits its own special characteristics. Whilst the scholarly prominence of academics can be based on more or less impersonal measures, especially citation statistics, academic celebrity, like popular celebrity, has emotional and subjective dimensions that call for non-subjective analysis. That challenge is met in this article by pointing to the cultural and institutional underpinnings of the phenomenon. In outlining some of academic celebrity’s defining features, we explore the critical difference between scholarly prominence, which is based on the perception of an academic’s excellence within their field, and celebrity, which incorporates adulation from colleagues and students. In reviewing the literature on the subject, we find models elaborating the ways in which modernity, in contrast to Elias’s court society (Rojek), or the world of aristocratic artistic patronage (Bourdieu), creates the conditions for the adulation of celebrities and the emergence of celebrity as an institution. We also find views critical of both the vulgarising effect of celebrity on literary and artistic taste (Coser), and its self-perpetuating character (Boorstin, Merton). Finally, we examine aspects of academic celebrity’s institutionalisation: the dynamic that drives the creation of new fields of specialisation within which academic celebrity is embedded, and the ‘managerial university’, which is said to generate and sustain it (Moran).